Developmental and Psychological Profile of Men Who Have Committed Sadistic Sexual Aggression against Women - Gauthier, Alexandre (Canadian journal of criminology and criminal justice, 2024)
The aims of the current study were twofold: (1) to identify factors that distinguish men who commit sadistic sexual aggression from those who do not; and (2) to investigate the developmental trajectories leading to sexual sadism. The study sample was composed of 206 men who had committed sexual aggression against women (69 men who had committed sadistic sexual aggression; 137 men who had committed nonsadistic sexual aggression), all of whom were incarcerated in Quebec (Canada). The Severe Sexual Sadism Scale (SESAS), an empirically validated instrument, was used to characterize the participants. Bivariate (χ2) analyses were performed. Our results revealed that men who had committed sadistic sexual aggression against women differed from others in several respects, notably developmental (e.g., emotional and physical abuse), psychological (e.g., avoidant and narcissistic personality profiles), sexological (e.g., deviant sexual fantasies), and criminological (e.g., a structured modus operandi, use of a weapon, anal penetration). Structural equation modeling analysis identified a developmental trajectory leading to the commission of sadistic sexual aggression. Theoretical and clinical implications of our results are discussed.